2008
DOI: 10.1598/rt.61.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Situated Identities: Power and Positioning in the Work of a Literacy Coach

Abstract: At 7:45 a.m. Kate (all names are pseudonyms) is already busy gathering materials to fill her cart that will serve as a mobile office today-her physical one will be used for make-up testing. Books, sticky notes, pens, and reflection sheets for grade-level meetings are first on her list. She shakes her head as she glances at the piles of running record assessments waiting to be collated, stapled, and distributed and the stacks of books waiting to be sorted, leveled, and placed on shelves. A teacher pops in and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 3 publications
2
56
0
Order By: Relevance
“…Several researchers have illustrated how a literacy coach's ability to perform a role can be limited by contextual factors (Chval et al, 2010;Hibbert et al, 2008;Lynch & Ferguson, 2010;Mangin, 2009;Matsumura, Garnier, Correnti, Junker, & Bickel, 2010;McLean, Mallozzi, Hu, & Dailey, 2010;Rainville & Jones, 2009;Smith, 2007).…”
Section: Contextualizing Literacy Coaches' Rolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have illustrated how a literacy coach's ability to perform a role can be limited by contextual factors (Chval et al, 2010;Hibbert et al, 2008;Lynch & Ferguson, 2010;Mangin, 2009;Matsumura, Garnier, Correnti, Junker, & Bickel, 2010;McLean, Mallozzi, Hu, & Dailey, 2010;Rainville & Jones, 2009;Smith, 2007).…”
Section: Contextualizing Literacy Coaches' Rolesmentioning
confidence: 99%
“…They argued that a focus on program implementation, dissemination of knowledge, and a forced hierarchy narrowed the role of the lead teachers and positioned other teachers as deficient. Rainville and Jones (2009) shared how one literacy coach enacted situated identities as she interacted with teachers in different ways according to a variety of expectations, relationships, and positions. Chval et al (2010) described how beginning mathematics coaches' identities were shaped by a negotiation between their own and others' expectations for their roles.…”
Section: Identity Power and Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…As the newly appointed literacy coach, Miss Tracey was responsible for laying the foundation for building genuine working relationships between herself and the teachers and amongst the groups of teachers so as not to replicate the resistance encountered by Kate in Rainville and Jones' (2008) recount. Without trusting relationships, teachers would not feel safe and comfortable in actively engaging in de-privatisation of their practice and a deep reflective process (Tanner & Vains-Loy, 2009).…”
Section: The First Yearmentioning
confidence: 99%
“…Another large-scale survey from across the United States documented that many school-based literacy coaches were expending 'a great deal of energy trying to create an identity' (Blamey, Meyer & Walpole, 2008, p. 122). Rainville and Jones' (2008) qualitative case-study also records the inherent tensions as literacy coaches negotiate their varied identities with different stakeholders. Another research study undertaken with 31 literacy coaches over a two year period by Walpole and Blamey (2008) found that 'what coaches should do on the job is the matter of intense debate and very little scholarship ' (p. 222).…”
mentioning
confidence: 99%